Adolescent borderline personality traits and dyadic behavior shape mother-adolescent cortisol synchrony - Fleck, Leonie; Fuchs, Anna; Lerch, Stefan; Möhler, Eva; Koenig, Julian; Resch, Franz; Kaess, Michael (Borderline Personality Disorder and Emotion Dysregulation, 2023)
Associations between parent and child cortisol levels (“cortisol synchrony”) are often reported and positive synchrony may mark dyadic regulation on a physiological level. Although dyadic behavior during interaction and adolescent borderline personality disorder (BPD) traits are linked with individual and dyadic regulatory capacities, little is known about how both factors influence parent-adolescent cortisol synchrony. We hypothesized that cortisol synchrony would differ depending on behavioral synchrony, i.e., smooth reciprocal dyadic interaction patterns, adolescent BPD traits, and their interactions.
Gesehen am 17.05.2023